Hydrogeophysical characterization of fractured aquifers for groundwater exploration in the Federal District of Brazil - Hussain, Yawar (2022)
The present study applies a geophysical approach to the Federal district of Brazil, a challenging hydrogeologic setting that requires improved investigation to enhance groundwater prospecting to meet the rising water demand. The geophysical characterization of a complex hard-rock aquifer sub-system was conducted using direct current (DC) electrical resistivity tomography (ERT) integrated with surface geological information. With a total of twenty-seven ERT profiles, the resistivity acquisition was carried out using a dipole-dipole array of electrodes with an inter-electrode spacing of 10 m. Based on resistivity ranges, the interpretation of the inverted resistivity values indicated a ground profile consisting of upper dry soil, saprolite, weathered, and fresh bedrock. Along with this layered subsurface stratigraphy, the approach allowed us to map the presence of significant hydrogeological features sharp contrasting anomalies that may suggest structural controls separating high-resistivity (≥7000 Ω m) and low-resistivity (<7000 Ω m) conducting zones in the uppermost 10 m of the ground. The assumed impacts of these features on groundwater development are discussed in light of the Brasilia aquifer settings.